Sistem Pakar Mendeteksi Penyakit Tanaman Terong Belanda dengan Menggunakan Metode Forward Chaining - Mikha Dayan Sinaga (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2014)
This expert system inference engine using forward chaining method. Reasoning is based on the symptoms that appear physically on the tree tomato. Based on these symptoms made rules which then becomes a knowledge base that will be applied to the inference engine to find out what the disease experienced by the Tree Tomato. The results of this program indicate that the expert system can be used as a medium that can provide information about the tree tomato. This expert system can be used to accelerate the search and access to knowledge by the people who need the information.